CanisTecOme: Canis lupus familiaris proteome database - Fernandes, M. (2015)
Introduction: The great amount of data generated by the omic sciences can only be explored and conjugated with other data using bioinformatics tools and databases. There is a great number of databases and dedicated bioinformatics tools to explore the proteomes, genomes and transcriptomes of several animals which interact with humans and therefore have an impact on the Health of several populations. Objective: The aim of the present work is the creation of a database with the molecular information available for Canis lupus familiaris. Such a tool will facilitate the identification of molecular mechanisms underlying physiological and physiopathological processes in dogs and therefore generates new opportunities for the design of therapeutical and diagnostic strategies. Methods: The development of this database is based on the manual compilation and review of the proteins identified in different studies using dog samples, with the annotation of the sample characterization and proteomics techniques used. Results: The database obtained is called CanisTecOme and includes proteins identified in proteomic and targeted studies published in the scientific literature from 2000 to 2013. Conclusion: We believe CanisTecOme and its publication with a web interface based on bioinformatics tools to explore the data, such as the OralCard available for the Human and previously developed, is a powerful instrument for the study of the physiology of this species.